Level of students` self-efficacy based on gender - Ifdil, Ifdil; Apriani, Rizka; Yendi, Frischa Meivilona; Rangka, Itsar Bolo (COUNS-EDU: The International Journal of Counseling and Education, 2016)
This research is aimed at describing the condition of both male and female students self-efficacy and identifying the difference. This research is a quantitative research with descriptive-comparative. The samples included 221 students. The data were analyzed by using descriptive statistics normal curve by determining the mean (average); calculating the percentage that exists in a particular category and analyzing t-test. The findings of the research showed 42.7% of male students self-efficacy are at moderate category of and 47.2% of female students are at high category. This research also revealed a significant difference of both female and male students self-efficacy. The implication of the research is it is expected that counselors provide guidance and counseling services to improve and develop self-efficacy, especially towards male students as self-efficacy of male students is lower than female students.